Enhancing humanistic skills: an experiential approach to learning about ethical issues in health care. Issue 1 (February 1995) - Sofaer, B
Abstract : An outstanding feature of the study of nursing ethics is that it raises questions concerning moral virtue, conscience, consistency and character. A considerable section of the literature is devoted to ideas of how best to teach ethics to health professionals. It has been shown that when faced with ethical dilemmas nurses tended to rely on intuition and instinct to resolve them, with little systematic analysis to help the process. Nurses who have been in practice for a number of years may experience particular difficulties in resolving ethical dilemmas, for although they may be able easily to identify ethical problems they may feel powerless to behave appropriately through lack of theoretical background and/or confidence in participating in informed debate. An educational programme was designed to meet the needs of mature registered nurses who were undertaking a post-qualification part-time honours degree in nursing studies. A variety of teaching methods were employed in teaching the nurses. These included discussion, student-led seminars, structured debate and role play. A session which dealt with sudden death and organ donation is described in some detail. Because the topic involved communication between professionals and patients and/or relatives and was linked with ethics, role play was used to explore the dynamics in these areas. The participants were invited to act out the situation as they felt it might occur. Role play highlighted the stress and shock attached to such an experience. Before working through the dynamics of a situation the nurses were conscious of being part of decision-making 'in the cold' and 'in isolation'. As a result of the experiential learning they felt more able to reflect analytically and to participate in discussions in an informed and articulate way.